Comparison of existing open-source tools for Web crawling and indexing of free Music - Serrão, C.; Ricardo, A. (Journal of Telecommunications, 2013)
This paper presents a portrait of existing open-source web crawlers tools that also have an indexing component. The goal is to understand what tool is best suited to crawl and index a large collection of music MP3 files freely available in the Internet. In this study each piece of software is briefly described, with an overview, identification of some users, and their main advantages and disadvantages. In order to better understand the most significant differences between the different tools a resume of features like: programming language in which they are written, the platform used for deployment, the type of index used, database integration, front-end capabilities, existence of a plugin system, MP3 and Adobe Flash (SWF files) parsing support, is presented. Finally the tools were classified according to the prospected collection size, being divided into tools to mirror small collections, medium and large collections with software capable of handling large amounts of data. In conclusion, an assessment on which tools are best suited to handle large collections in a distributed way is made.